Impedimetric analysis of the effect of decellularized porcine heart scaffold on human fibrosarcoma, endothelial, and cardiomyocyte cell lines - Bäcker, Henrik Constantin; Szabó, Gábor; Weymann, Alexander (Medical science monitor, 2017)
BACKGROUND Experiments on porcine heart scaffold represent significant assays in development of immunoneutral materials for cardiac surgery. Characterization of cell-cell and cell-scaffold interactions is essential to understand the homing process of cardiac cells into the scaffolds. MATERIAL AND METHODS In the present study, the highly sensitive and real-time impedimetric technique of xCELLigence SP was used to monitor cell adhesion, which is the key process of recellularization in heart scaffolds. Our objectives were: (i) to characterize the effect of decellularized porcine heart scaffold on cell adhesion of human cardiovascular cells potentially used in the recellularization process; and (ii) to investigate cell-extracellular matrix element interactions for building artificial multi-layer systems, applied as cellular models of recellularization experiments. Human fibrosarcoma, endothelial, and cardiomyocyte cells were investigated and the effect of decellularized porcine heart scaffold (HS) and fibronectin on cell adhesion was examined. Adhesion was quantified as slope of curves. RESULTS Heart scaffold had neutral effect on cardiomyocytes as well as on endothelial cells. Adhesion of cardiomyocytes was increased by fibronectin (1.480±0.021) compared to control (0.745±0.029). The combination of fibronectin and HS induced stronger adhesion of cardiomyocytes (2.407±0.634) than fibronectin alone. Endothelial and fibrosarcoma cells showed similarly strong adhesion profiles with marked enhancer effect by fibronectin. CONCLUSIONS Decellularized porcine HS does not inhibit adhesion of human cardiovascular cells at the cell biological level, while fibronectin has strong cell adhesion-inducer effect, as well as an enhancer effect on activity of HS. Consequently, decellularized porcine hearts could be used as scaffolds for recellularization with cardiomyocytes and endothelial cells with fibronectin acting as a regulator, leading to construction of working bioartificial hearts.